EVALUASI KEBIJAKAN PENGELOLAAN SAMPAH PLASTIK DI KOTA SEMARANG - Primanto, Aji; Puspitasari, Linda (CV. Lafadz Jaya, 2025)
The population growth in Semarang City over the years has directly contributed to the increasing volume of waste, particularly plastic waste, which is non-biodegradable and harmful to the environment. Between 2020 and 2024, data indicates a significant rise in plastic waste generation alongside more frequent flooding, particularly in densely populated areas and along riverbanks. This study aims to evaluate the effectiveness of plastic waste management policies in Semarang City by applying William N. Dunn’s (2018) policy evaluation framework, which includes five dimensions: effectiveness, efficiency, adequacy, equity, and responsiveness. A qualitative approach was used, employing a literature review, policy document analysis, and spatial data visualization (heatmaps) to identify correlations between flood-prone areas and plastic waste accumulation. The findings reveal that despite the issuance of several local regulations on plastic reduction and waste management, implementation faces persistent challenges, such as low public participation, inadequate waste transportation infrastructure, and weak enforcement on businesses and industries. Evaluation through Dunn’s five dimensions indicates that the policy has not yet achieved optimal effectiveness and efficiency, as its direct impact on reducing plastic waste and mitigating flood risks remains limited. This research recommends renewing more adaptive policies, strengthening institutional capacity, and integrating spatial data-based waste management systems as strategic steps for sustainable improvement.